2015
DOI: 10.22421/1517-7130.2015v16n4p64
|View full text |Cite
|
Sign up to set email alerts
|

Análise dos aspectos epidemiológicos da dengue: implicações para a gestão dos serviços de saúde

Abstract: Objetivo: Descrever o perfil epidemiológico da dengue na microrregião de saúde de Salvador, Bahia, período de 2007 a 2014, e sua relação com as características socioeconômicas dos municípios. Método: Trata-se de um estudo ecológico espaço-temporal, tendo como unidades de análise municípios e ano, a partir dedados secundários. Os dados foram analisados de forma descritiva e estatística através do Coeficiente de Correlação de Spearman. Resultados: Foram confirmados 56.921 casos de dengue, compredomínioda incidên… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 8 publications
1
3
0
5
Order By: Relevance
“…Planalto followed with 3,714 positive properties in the six years studied, with the highest number of properties in 2013 (1,144), reflected in the high HI present by this municipality, in the 2013 this number reached 12.64, and also maintained the Risk of Outbreak (HI > 3.9%) throughout all years analyzed. Salvador (2012) and Rio de Janeiro 2011-2013cities also recorded high numbers of DENV cases in same years of our study, indicating an alignment of our data with other locates (Martins et al 2015, Xavier et al 2017. Regarding the Prevalence Index of DENV cases, Vitória da Conquista and Planalto had a PI of 1.16%.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Planalto followed with 3,714 positive properties in the six years studied, with the highest number of properties in 2013 (1,144), reflected in the high HI present by this municipality, in the 2013 this number reached 12.64, and also maintained the Risk of Outbreak (HI > 3.9%) throughout all years analyzed. Salvador (2012) and Rio de Janeiro 2011-2013cities also recorded high numbers of DENV cases in same years of our study, indicating an alignment of our data with other locates (Martins et al 2015, Xavier et al 2017. Regarding the Prevalence Index of DENV cases, Vitória da Conquista and Planalto had a PI of 1.16%.…”
Section: Discussionsupporting
confidence: 88%
“…Also, the virus can alter its epidemic potential and clinical manifestations when it moves between populations; which causes the infection epidemic to appear differently (Teixeira et al 1999). In line with this study, cities like Salvador (2012) and States like Paraíba (2013) and Goiás (2012-2013) also R. Largo 1.02 0.00 0.00 0.00 0.00 * 0.20 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 recorded in these years cited, the largest number of confirmed cases for Dengue (Fantinati et al 2013, Martins et al 2015, Guerra-Gomes et al 2017. From 2010 to 2015, the municipalities with the highest numbers of positive properties per year were Vitória da Conquista and Planalto.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This is in agreement with the findings of Martins et al in relation to Salvador, capital of the state of Bahia, for the period 2007-2014. 16 By grouping cases together as classic cases and non-classic cases, we found that the percentage of cases classified as non-classic (DCC, DHF, DSS, DSCA and SD) is almost five times greater than that found on the municipal SINAN for the same period, when 0.3% of cases were non-classic. A study conducted in a public hospital in Rio de Janeiro, RJ, in 2008, during one of the biggest epidemics recorded in that municipality, found 6.7% non-classic cases.…”
Section: Discussionmentioning
confidence: 66%
“…Figura 1-Taxa de incidência (casos/100 mil habitantes) da dengue por sexo no Mato Grosso, Brasil, 2001. 2001200220032004200520072008200920102011201220132015Total Masculino 91,20 323,20 313,50 80,60 207,70 288,60 501,60 213,70 1544,1 1101 (2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018) houve variação das taxas de letalidade entre anos, seja para sexo e no geral (Figura 2). Vieram a a óbitos 256 pessoas, sendo 154 do sexo masculino e 102 do sexo feminino (Figura2).…”
Section: Taxa De Incidência Por Sexounclassified